Effect of Sesame Oil on Lipid Profile and Liver Enzymes in Male Albino Rats Treated With Carbone Tetrachloride (CCl4) - Abdul-Lattif, Rashaa Faiq (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
This study was designed to investigate the effect of sesame oil on lipid profile and liver enzyme in male albino rats treated with Carbone tetrachloride (CCl4). Forty adult male rats were divided into four equal groups, first group was daily administrated with tap water, the second group was injected with CCl4 (80mg/kg.BW/day), the third group was administrated with sesame oil (150mg/kg.BW/day) and the fourth group was injected with CCl4 (80mg/kg.BW/day) and was administrated with sesame oil (150 mg /kg.BW /day) for 30 days. The statistical results of the present study showed a significant (p<0.05) increase in the level of cholesterol , triglycerides and Low density lipoprotein (LDL) in the group treated with CCl4 compared with control group, also a significant (p<0.05) increase in the level of liver enzymes Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) , no difference on High density lipoprotein (HDL) level .The fourth group that was administrated with sesame oil and injected with CCl4 showed a significant (p<0.05) decrease in the level of cholesterol, triglyceride , LDL and also a significant (p<0.05) decrease in liver enzymes Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) compared with the group that injected with Carbone tetrachloride CCl4. It is concluded that sesame oil has a protective effect against the toxicity of Carbone tetrachloride on the liver.